SEISMOTECTONIC ANALYSIS OF VIRAAYOTS-KARABAKH ZONE WITH THE AIM OF HIGHLIGHTING OF THE EARTHQUAKE PRONE BLOCKS (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
In this article seismotectonic activity of Viraayots-Karabakh (Somkheto-Kapan) geotectonic zone was analysied. Using modern tectonic-geomorphological methods, the Neotectonic (Neogene-Quaternary) activity of blocks was analyzed and they were classified according to this indicator. As the block model of the territory a large-scale scheme of morphostructural zoning of the territory of Armenia was used, which shows all main lineament-block formations of the territory. Current seismicity of the territory, which is based on statistical analysis of registered here seismic events of different strength, was analyzed. Released total seismic energy for each individual block was counted. In the result general patterns of seismotectonic activity and certain spatial patterns of seismicity of Viraayots-Karabakh tectonic zone were highlighted, based on what strong earthquake prone blocks were selected.
Keywords: block structure; tectonic activity; seismic activity; earthquake prone blocks